2021
DOI: 10.1002/epi4.12454
|View full text |Cite
|
Sign up to set email alerts
|

Super refractory status in a case of Febrile Infection‐Related Epilepsy Syndrome due to hemophagocytic lymphocytic histiocytosis

Abstract: A 14‐year‐old boy presented with a prodromal respiratory infection followed by super refractory status epilepticus. A diagnosis of Febrile Infection‐Related Epilepsy Syndrome (FIRES) was made. Initial MRI study and CSF analysis were normal. He required multiple anticonvulsants owing to the refractory nature of the seizures. The course of the illness was rather stormy, laced with various medical problems viz. hepatic dysfunction, sepsis, hemodynamic, and hematological abnormalities which posed several challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Five out of 19 studies viz. Mewasingh et al, Liaqat et al, Caranzano et al, Basha et al and Meenakshi-Sundaram et al reported on recurrence of seizures either during hospitalization (10 patients) or during follow up (1 patient) after ketamine treatment [ 17 , 20 , 21 , 24 , 30 ]. Among ten patients, further treatment with either ketamine or propofol or surgical intervention led to resolution of seizures.…”
Section: Resultsmentioning
confidence: 99%
“…Five out of 19 studies viz. Mewasingh et al, Liaqat et al, Caranzano et al, Basha et al and Meenakshi-Sundaram et al reported on recurrence of seizures either during hospitalization (10 patients) or during follow up (1 patient) after ketamine treatment [ 17 , 20 , 21 , 24 , 30 ]. Among ten patients, further treatment with either ketamine or propofol or surgical intervention led to resolution of seizures.…”
Section: Resultsmentioning
confidence: 99%
“…Haemophagocytic lymphohistiocytosis (HLH) is a rare haematological syndrome of severe immune activation with macrophage and T-cell infiltration resulting in multiorgan damage. The association of HLH and FIRES has been described in paediatric patients by Farias-Moeller et al and Meenakshi-Sundaram et al 2 3. We describe the management of an adult patient with FIRES and HLH.…”
Section: Introductionmentioning
confidence: 68%
“…Of the remaining two patients, one had moderate cognitive impairment, and the other was dependent on all activities of daily living. Meenakshi-Sundaram et al reported a 14-year-old with FIRES and secondary HLH, with viral illness 9 days before admission 2. The patient died despite chemotherapy and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%